Domiciliary Care Providers Views on Provision of Palliative Care for their Cancer Patients - MKDL, Meegoda; DMS, Fernando; S, Sivayogan; NOS, Atulomah; RB, Marasinghe (Cancers Review, 2018)
A qualitative study was conducted to describe views and life experiences of domiciliary care providers in meeting the palliative care needs of adult cancer patients at the National Cancer Institute, Maharagama, Sri Lanka. The target population for this study was Domiciliary Care Providers (DCPs) who were the family care givers of patients at National Institute of Cancer, Maharagam (NICM), Cancer Home (CH), Maharagama, Shantha Sevana Hospice (SSH) and Ceylinco Oncology Unit (COU), Colombo, Sri-Lanka. Purposive sampling technique was used to select participants for the study. In-depth interviews were conducted using validated semi-structured interviewer guide. Data saturation was reached after 15 in-depth interviews with DCPs. Trustworthiness of the study was maintained. Phenomenological-hermeneutic approach was followed to analyze qualitative data and thematic analysis was performed. Data analysis was done concurrently with data gathering. Being reassured, having more expectations, need psychosocial help and inadequate knowledge were the key themes identified. They expect knowledge improvement to provide better care. As patients’ level of satisfaction on domiciliary care provided by DCPs was high, improving their knowledge on palliative care may be a cost effective method of improving palliative care.